Changing The Largest Force of Inequality by Ruqayya in Radwa Ashour's The Woman from Tantoura - Bella Cintya Nur Halizza; Suci Suryani (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2022)
Women as victims of sexist oppression become a global issues up to now. One of the causes that lead to women being victims of sexist oppression is a patriarchy system that is still developing. This study aims to analyse Ruqayya’s strength in dealing with various kinds of pressure as a Palestinian woman in Radwa Ashour’s The Woman from Tantoura. Furthermore, three issues will be investigated in this study, those are; kinds of sexist oppression experienced by Ruqayya, how solidarity is formed by sharing sources and how solidarity forms a unity front for the emergence of Ruqayya’s power practices to stop sexist oppression. This study is qualitative design because the data are collected in the form of words. The data of this study are the narrator’s explanations and the character’s utterances related to the three issues above. The results of the analysis show that Ruqayya experiences kinds of sexist oppression such as arranged marriages, violence, and sexual abuse. Ruqayya forms a bond of solidarity built on empathy and sharing sources. Ruqayya obtains power from the bond so that the action is formed by Ruqayya as her resistance to end sexist oppression.